Investigation of flood capability in Jafarabad basin - Shamsollah Asgari; Amir Safari (تحقیقات کاربردی علوم جغرافیایی)
One of the important and effective factors in the destruction of natural resources is the flood phenomenon, identification of this phenomenon and effective parameters in flood occurrence in natural resources and catchment areas is necessary. The purpose of this study was to determine the flooding of sub-basins in Jafarabad basin in Ilam province. In this research, the Jafarabad basin in Ilam Province is divided in to 12 sub-basins. For each sub-basin, 28 geometric, climatic, permeable and physiographic parameters such as area, environment, length and slope of main stream, length and slope of the basin, time of concentration, The coefficients of shape and variability of precipitation, vegetation cover, CN, discharge and ... have been calculated using GIS software. Factor analysis was used to determine the flood potential of the sub basins. The data of 28 sub-basin variables were analyzed by SPSS software and summarized in 5 main factors (shape, flow, slope, drainage and runoff). The results indicate that the factor of the form with a specific value of 11/30 is the most important factor in the flooding of the studied basin. Channel, slope, drainage and runoff factors with a specific value of 7.21,4.34,3.22 and 3.10 respectively Priority is in the next rank. Then, based on the factor scores of the study area, three large, medium and low flooding categories were mapped and a zoning map of the flood potential of the sub-basins was drawn in the GIS environment. Sub-basins (9,8,5,3) in the shape of the sub-basins (1,6,11) in the gradient factor, sub-basins (2, 7) in the drainage factor and in the runoff factor of the sub-basins (4,10,12 ) Have a lot of flood potential. In sub-basins, the similarity of flooding, erosion, vegetation, and human performance impacts is divided into 3 groups with high, medium and low flood potential. Sub-basins play a major role in the flooding of the basin, which affects the vast agricultural fields of the lower reaches.